220Rn (Thoron) Geohazard in Room Air of Earthen Dwellings in Vietnam. (2nd May 2019) - Nguyễn-Thuỳ, Dương; Nguyễn-Văn, Hướng; Schimmelmann, Jan P.; Nguyễn, Nguyệt Thị Ánh; Doiron, Kelsey; Schimmelmann, Arndt
Abstract : Thoron's ( 220 Rn) contribution to α -radiation exposure is usually considered negligible compared to that of 222 Rn (radon). Despite its short half-life of 55.6 seconds, thoron can be exhaled from porous surface layers of building materials into indoor air where people subsequently inhale radioisotopes, including metallic radioactive progeny. Bare surfaces of dry porous soil with relatively high 232 Th content can pose a thoron radiation hazard in indoor air. On northern Vietnam's Đồng Văn karst plateau, the spatial distribution of thoron was determined in indoor air of traditional earthen and other types of dwellings using portable RAD7 and SARAD® RTM 2200 detectors. "Mud houses" are constructed with local compacted soil and typically do not have any floor or wall coverings (i.e., no plaster, wallpaper, or paint). Detailed measurements in a mud house revealed levels of thoron in room air averaging >500 Bq m -3 . The spatial distribution of α -radiation from thoron in indoor air at a distance of about 1 m from interior walls was fairly homogeneous and averaged 200 Bq m -3 . Most concerning, from a human health perspective, were the high thoron concentrations of up to 884 Bq m -3 in sleeping areas near mud walls. The average annual thoron radiation dose to inhabitants of mud houses was estimated based on 13 hours of daily occupancy, including daily activities and sleeping. The estimated average thoron inhalation dose of 27.1 mSv a -1 during sleeping hours near mud surfaces accounts for nearly 75% of the total estimated radon and thoron inhalation dose of 37.4 mSv a -1 from indoor mud house air. Our conservative annual radiation dose estimates do not include subsequent radiation from inhaled metallic progeny of thoron. Our data demonstrate a significant human health risk from radiation exposure and a critical need for remediation in traditional northern Vietnamese mud house dwellings.